Contextual Teaching And Learning (CTL) Sebagai Model Pembelajaran Ekonomi dalam KBK - Sihono, Teguh (Jurnal Ekonomi dan Pendidikan, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>Curriculum based on competency is a curriculum design developed based on a set of certain competencies. In Indonesia, -so far- education is dominated by idea saying that knowledge is a set of facts that have to be memorized. Classes focus on teacher as a main source of knowledge. It is need to find a new teaching and learning method so that it can develop student involvement. Contextual Teaching and Learning is a new strategy promoted, since this strategy is claimed can encourage students to construct knowledge into their own mind.